2009
DOI: 10.1161/circulationaha.108.805804
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Modulation of Cardiac Ryanodine Receptor Activity Is Associated With Downregulation of FK506-Binding Proteins

Abstract: Background-The mineralocorticoid pathway is involved in cardiac arrhythmias associated with heart failure through mechanisms that are incompletely understood. Defective regulation of the cardiac ryanodine receptor (RyR) is an important cause of the initiation of arrhythmias. Here, we examined whether the aldosterone pathway might modulate RyR function. Methods and Results-Using the whole-cell patch clamp method, we observed an increase in the occurrence of delayed afterdepolarizations during action potential r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 51 publications
5
72
0
Order By: Relevance
“…36 Given that higher aldosterone levels in PHA1 may reflect a more severe impairment of MR function, the finding of a better LV systolic function in the upper quartile of aldo in Cs further supports the central role of MR signaling in mediating deleterious CV effects of aldo. The mechanisms involved in the effects on diastolic function were not addressed in our study but could be related to changes in L-type calcium channel activity, as reported in cellular models 37 and in mice overexpressing MR in cardiomyocytes, 16,38 or to MR effects on cardiac endothelial function. 39 Homozygous MR knockout mice recapitulate the renal phenotype of a severe renal PHA1, which can be rescued by Na supplementation.…”
Section: Discussionmentioning
confidence: 92%
“…36 Given that higher aldosterone levels in PHA1 may reflect a more severe impairment of MR function, the finding of a better LV systolic function in the upper quartile of aldo in Cs further supports the central role of MR signaling in mediating deleterious CV effects of aldo. The mechanisms involved in the effects on diastolic function were not addressed in our study but could be related to changes in L-type calcium channel activity, as reported in cellular models 37 and in mice overexpressing MR in cardiomyocytes, 16,38 or to MR effects on cardiac endothelial function. 39 Homozygous MR knockout mice recapitulate the renal phenotype of a severe renal PHA1, which can be rescued by Na supplementation.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, our findings reveal a previously unidentified role for Ang-(1-7) as a modulator of diastolic Ca 2+ sparks in the heart under conditions of elevated aldosterone levels. In fact, Gomez et al 9 have shown that aldosterone directly affects RyR activity, by dissociating FKBP12.6, leading to abnormal Ca 2+ sparks in ventricular myocytes. Aberrant Ca 2+ release during diastole has been linked to the development of cardiac arrhythmia in heart failure models.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, aldosterone upregulates L-type Ca 2+ current (I Ca ), 7 enhances cardiomyocyte shortening, 8 and increases ryanodine receptor (RyR) activity leading to abnormal Ca 2+ release in ventricular myocytes. 9 Previously, it has been shown in vivo that angiotensin (Ang)-(1-7) infusion protects the heart against deoxycorticosterone acetate-mediated cardiac dysfunction. 10 Similar findings were observed in a transgenic rat with increased circulating levels of Ang-(1-7).…”
mentioning
confidence: 99%
“…Furthermore, MR overexpression decreased heart rate variability and induced ion channel remodelling: decreased transient outward potassium current (Ito) activity and increased L-type calcium channel stimulation [40]. Similarly, numerous studies have explored modulation of electrical activity by MR activation, the pro-arrhythmogenic effect of aldosterone and the associated benefit of MR antagonists [41][42][43][44]. Recently, in a low-aldosterone hypertension model, Dahl salt-sensitive (DS) rats, Kimura et al [45] have shown that MR inhibition with eplerenone reversed structural remodelling and atrial fibrillation.…”
Section: Genetic Mr Manipulationmentioning
confidence: 99%